Using The Problem Posing Learning Model Based On Open Ended To Improve Mathematical Critical Thinking Ability - Sapta, Andy; Pakpahan, Sondang Purnama; Sirait, Syahriani (Journal of Research in Mathematics Trends and Technology, 2019)
The problem of this study is the low student mathematics learning outcomes caused by the lack of critical ability. The purpose of this study is to use the problem posing learning model based on open ended to improve mathematical critical thinking abilities. The population is the second semester of Asahan University students, amounting to 110 people. The sample is obtained using the cluster random sampling method. The study sample was two classes from 3 classes. The implementation of this research by giving use the problem posing learning model based on open ended. Data collection techniques by giving tests to students who are sampled. The research data shows that by applying the use of the problem posing learning model based on open ended to improve athematic critical thinking abilities in participating in probability courses.